1998
DOI: 10.1007/bf02937419
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis a in urban Ireland

Abstract: This study concludes that urban Ireland is an area of low HAV endemicity with age and socioeconomic status as the significant influences on seropositivity. This survey provides an insight into the changing epidemiology of HAV infection in Ireland and serves as a guide for immunisation of at risk population groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
2
1
1
Order By: Relevance
“…Rajaratnam et al (1992) and Leoni et al (1998) revealed that the school toilets were the source of transmission of HAV infection. In this study we observed a higher prevalence of anti-HAV antibodies in children at lower socioeconomic status, as also reported by Rajan et al (1998) and Riedemann et al (1998). Although they have reported to have sewage disposal and water supply system, we can not affirm that these children live in homes with adequate conditions of hygiene.…”
Section: Discussionsupporting
confidence: 91%
“…Rajaratnam et al (1992) and Leoni et al (1998) revealed that the school toilets were the source of transmission of HAV infection. In this study we observed a higher prevalence of anti-HAV antibodies in children at lower socioeconomic status, as also reported by Rajan et al (1998) and Riedemann et al (1998). Although they have reported to have sewage disposal and water supply system, we can not affirm that these children live in homes with adequate conditions of hygiene.…”
Section: Discussionsupporting
confidence: 91%
“…Susceptibility to hepatitis A infection among this PLWH cohort is lower than what has been previously described (33%) in the general Irish population ( 26 ). Hepatitis A IgG seronegativity was significantly less likely to be seen in older attendees and those whose HIV acquisition status was PWID, possibly due to prior vaccination though exposure to infection is also a possibility.…”
Section: Discussioncontrasting
confidence: 77%
“…In the Czech Republic and Slovenia only about half of adults have been infected by age 40 [117,176]. In the late 1980s in Leningrad (now St Petersburg), Russia, >50 % of age 35+ Czech Republic [117] 4 % in age <20 ; 50 % in ages 40-49; >85 % in age 60+ Denmark [151] <10 % of ages 15-34; 50 % of ages 50-69 Finland [184] <10 % of ages 20-29 France [133] 29 % in ages 20-29; >90 % by age 60 Germany [182] 14 % in ages 18-29; 64 % in ages 50-59 Greece [146,152] <10 % of children; >90 % by age 45 Hungary [165] <20 % in children; >50 % by age 40 Iceland [122] <5 % of ages 10-50 Ireland [168,170] 19 % of ages 5-14; >90 % of age 45+ Italy [160,190] <10 % in young adults ; >90 % by age 50 Netherlands [181] <10 % in young adults ; 50 % by age 45 Norway [175] <10 % in adults ages 20-40 Poland [127,166] <10 % in children; >75 % by age 40 Portugal [116] 21 % of ages 6-7 ; 38 % of ages 18-19 Romania [161] >50 % of ages 5-9 ; >90 % by age 30 Russia [174] >50 % by age 20 San Marino [179] 29 % of ages 20-30; >90 % by age 40 Spain [129] 25 % of ages 13-19; 55 % of ages 20-29; >90 % by age 30 Sweden [121] 2 % in adults ages 20-50 United Kingdom [139,159] 9 % in ages 1-9 ; >60 % in ages 50-59…”
Section: The Americasmentioning
confidence: 99%
“…In England the rate has fallen from the late 1970s [131] to the mid-1980s [139] to the mid-1990s [118,159]. No decline was seen in Ireland [168,170]. Rates in Germany have declined [137,182], but significant differences are still seen between East and West Germans [182].…”
Section: The Americasmentioning
confidence: 99%